The Role of Technology in Education Sector at Digital Era - Anita Candra Dewi; Anggun Citra Bahar; Selfi; Fina; Flower Sappe Amy; Muhammad Adriyan.A; Erik Francis Tandi (MultiTech Publisher, 2023)
Technology is a tool, machine, material, and process that is constantly developed and applied to help facilitate humans in solving various problems. In accordance with the focus of this study is to know the role of technology on the field of education in the digital age. And there are two destinations, the first of the field of education in general and the field of education in particular in this case college. The method used in this research is the library research) with the results of the study of the translation of the technology role in the field of public scares education and specifically the field of education of college.